Sharing experiences and developing collaboration to integrate gender in breeding programs. - Polar, Vivian (2019)
RTB as leader of the Gender and Breeding initiative has been interacting with the Excellence in Breeding Platform EiB to promote a formal integration of gender into product profile development processes. Currently, there are some tools available from the Gender and Breeding Initiative that will be piloted with some breeding programs. On the other hand, many breeding programs are also working with a variety of tools and approaches on initiatives like ABACUSBIO Ltd., RTBfoods, and others. The objective of the meeting is to share different experiences and tools used to integrate social differentiation and gender into product profile development and to develop collaboration within and between different researchers in the breeding programs.